2021
DOI: 10.1186/s12939-021-01547-7
|View full text |Cite|
|
Sign up to set email alerts
|

Inequalities in population health loss by multiple deprivation: COVID-19 and pre-pandemic all-cause disability-adjusted life years (DALYs) in Scotland

Abstract: Background COVID-19 has caused almost unprecedented change across health, education, the economy and social interaction. It is widely understood that the existing mechanisms which shape health inequalities have resulted in COVID-19 outcomes following this same, familiar, pattern. Our aim was to estimate inequalities in the population health impact of COVID-19 in Scotland, measured by disability-adjusted life years (DALYs) in 2020. Our secondary aim was to scale overall, and inequalities in, COV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The majority of the population health loss was due to mortality as it represented 95% of DALYs 16 YLL per Covid-19 death. On comparing to the Scottish Covid-19 BoD study, our study's mortality contributed to a lesser percentage to the DALYs than Scotland, where the latter reported mortality to contribute to 98% of DALYs [22].…”
Section: Discussionmentioning
confidence: 55%
“…The majority of the population health loss was due to mortality as it represented 95% of DALYs 16 YLL per Covid-19 death. On comparing to the Scottish Covid-19 BoD study, our study's mortality contributed to a lesser percentage to the DALYs than Scotland, where the latter reported mortality to contribute to 98% of DALYs [22].…”
Section: Discussionmentioning
confidence: 55%
“…Integrating the impact of inequality both within- and across-countries is important as we progress our work. Evidence has indicated that socioeconomic inequality-attributable COVID-19 DALYs are 40% in Scotland, a result which has been borne out of a legacy of systemic inequality ( 41 ). As the pandemic has evolved, monitoring inequalities within countries will give indications into how successful attempts have been to mitigate inequalities, e.g., by prioritizing certain groups for vaccination before others.…”
Section: Discussionmentioning
confidence: 99%
“…Population health in Europe is not improving in a uniform way. Socioeconomic health inequalities have largely persisted over the last decade, with varying patterns of trends across European countries [1,2]. Successful actions against health inequalities rest on the ability to measure and understand the problem on one hand, and to follow up on the impact of actions on the other [3].…”
Section: Introductionmentioning
confidence: 99%